Views of Bonn & the Seven Mountains ascending the Rhine and the city of Cologne. - Johnson, Joseph (publisher):::::::::::::::; Payne, John (author)::::::::::::::: (United Kingdom; Published by J. Johnson; London)
Engravings of Bonn and the Siebengebirge, and the city of Cologne, from ca. 1793.